Recommendations for COPD management in Central and Eastern Europe. Issue 2 (1st February 2022) - Valipour, Arschang; Aisanov, Zaurbek; Avdeev, Sergey; Koblizek, Vladimir; Kocan, Ivan; Kopitovic, Ivan; Lupkovics, Gergely; Man, Milena; Bukovskis, Maris; Tudoric, Neven; Vukoja, Marija; Naumnik, Wojciech; et al.
ABSTRACT: Introduction: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy report provides guidance on effective management of chronic obstructive pulmonary disease (COPD) according to local healthcare systems. However, COPD is a heterogenous disease and certain aspects, including prevalence, disease–time course and phenotype distribution, can differ between countries. Moreover, features of clinical practice and healthcare systems for patients with COPD can vary widely, even in geographically close and economically similar countries. Areas covered: Based on an initial workshop of respiratory physicians from eleven countries across Central and Eastern Europe (CEE) in December 2018 and subsequent discussions, this article offers region-specific insights from clinical practice and healthcare systems in CEE. Taking recommendations from the GOLD 2022 report into account, we suggest approaches to adapt these into national clinical guidelines for COPD management in CEE. Expert opinion: Several factors should be considered when optimizing management of COPD in CEE compared with other regions, including differences in smoking status, vaccination uptake, prevalence of tuberculosis and nontuberculous mycobacteria, and variations in healthcare systems. We provide guidance and algorithms for pharmacologic and non-pharmacologic management of COPD for the following scenarios: initial and follow-up treatment, treatment of patients with frequent exacerbations, and withdrawal of inhaled corticosteroids where appropriate. PLAIN LANGUAGE SUMMARY: Chronic obstructive pulmonary disease (COPD) is a common disease of the lungs. It causes symptoms such as breathlessness, cough, and production of phlegm. In people with COPD, these symptoms often reduce the quality of their lives. From time to time, symptoms may get worse in people with the disease. This worsening is known as 'exacerbation'. Exacerbations of COPD can be so bad that they lead to hospital admissions. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) regularly gives advice to doctors around the world. This can help them to provide their patients with the best possible treatment for COPD. However, people with the disease and healthcare systems vary from country to country. This means that the guidance may need to be adjusted to the needs and available resources of different regions. This review looks at how COPD is treated in Central and Eastern Europe. We suggest how to adapt the GOLD recommendations to best suit the Central and Eastern European region. Graphical Abstract: uf0001